2017
DOI: 10.1103/physrevlett.118.221802
|View full text |Cite
|
Sign up to set email alerts
|

Observation of ψ(3686)e+eχcJ and et al.

Abstract: Observation of psi(3686) -> e(+)e(-)chi(cJ) and chi(cJ) -> e(+)e(-)J/psi

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…In [15] it was shown that the branching fractions of these decays and distributions over the invariant mass of ( ) pair can be calculated using very general assumptions on the basis of experimentally known branching fractions of the corresponding radiative decays χ cJ → J/ψγ and χ bJ → Υγ (see also [16][17][18][19]). Currently only χ c1,2 → J/ψee process was studied experimentally [20]. It could be interesting also to consider muon pair production in χ cJ → J/ψµµ and χ bJ → Υµµ decays.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In [15] it was shown that the branching fractions of these decays and distributions over the invariant mass of ( ) pair can be calculated using very general assumptions on the basis of experimentally known branching fractions of the corresponding radiative decays χ cJ → J/ψγ and χ bJ → Υγ (see also [16][17][18][19]). Currently only χ c1,2 → J/ψee process was studied experimentally [20]. It could be interesting also to consider muon pair production in χ cJ → J/ψµµ and χ bJ → Υµµ decays.…”
mentioning
confidence: 99%
“…χc2) ee Br (χc2) γ = 8.7 × 10 −3 , Br (χc2) ee Br (χc2) γ exp= (11.3 ± 0.4 ± 0.5) × 10 −3 . (6)arXiv:1709.02444v1 [hep-ph] Q distribution in comparison with BESSIII data[20,21] Normalized Q 2 distribution for χcJ → J/ψµµ (left figure) and χ bJ → Υµµ (right figure) decays…”
mentioning
confidence: 99%
“…The branching fractions for χ cJ → μ þ μ − J=ψ are predicted in Ref. [6] (Throughout this paper, χ cJ refers to χ c0 , χ c1 , and χ c2 ), and it is demonstrated that the μ þ μ − decay channels are more suitable for the investigation of χ cJ → γ Ã J=ψ decay vertices than e þ e − decay channels, which have been observed at BESIII [7]. Very recently, LHCb reported the observation of χ c1;2 → μ þ μ − J=ψ [8] and measured the χ c1;2 resonance parameters.…”
Section: Introductionmentioning
confidence: 88%
“…The helicity angle distribution 1 þ α • cos 2 θ of the μ þ μ − pair in χ cJ rest frame may affect the detection efficiency, where α is angular distribution parameter. We fix the angular distribution of μ þ μ − pair in χ c1;2 → μ þ μ − J=ψ at the measurements from processes χ c1;2 → e þ e − J=ψ [7], α χ c1 ¼ 0.0 AE 0.2 and α χ c2 ¼ 0.5 AE 0.2, and vary 1σ to get the systematic uncertainty. For the decay χ c0 → μ þ μ − J=ψ, the angular distribution of μ þ μ − pair is set to be flat, and varied to 1 AE cos 2 θ to get the systematic uncertainty.…”
Section: Systematic Uncertaintymentioning
confidence: 99%
“…Recently, both BESIII [6,7] and LHCb [8] have observed the dilepton EM decays of χ cJ and ψ(3686), where χ cJ refers to χ c0 , χ c1 and χ c2 . By analysing the cascade decays of ψ(3686) → χ cJ e + e − , χ cJ → J/ψγ and ψ(3686) → χ cJ γ, χ cJ → J/ψe + e − , the BESIII Collaboration measured the branching fractions of χ cJ → J/ψe + e − , which are (1.51 ± 0.30 ± 0.13) × 10 −4 , (3.73 ± 0.09 ± 0.25) × 10 −3 , (2.48 ± 0.08 ± 0.16) ± 10 −3 [6]. This has been gradually bringing more attention on such decays.…”
Section: Introductionmentioning
confidence: 99%